John Senders (1920-2019) - Hancock, Peter A.; Hancock, Gabrielle M.; Sanders, W.; Sellen, Abigail (The American Journal of Psychology, 2019)
Excerpt: We here survey and applaud the life and scientific contributions of John W. Senders. Encompassing almost a century of experience, Senders’s interests embraced vast swathes of knowledge, and he was at home in all of them. Most concerned with the application of solid experimental methods in pursuit of solutions to highly practical, real-world problems, Senders conceived of and created many of the approaches we today consider standard. His work on visual scanning still resonates in our modern world through the promulgation of national and international standards.